Kolaborasi Multi Stakeholder Dalam Menjaga Destinasi Wisata Pantai Loang Baloq - Hidayat, Rahmad; Pratama, Inka Nusamuda (STMIK Royal, 2023)
The community service activities carried out are a multi-stakeholder collaborative effort in maintaining the cleanliness and sustainability of Loang Baloq Beach. The activity was carried out by involving various related parties, including the Regional Government, PDPM Mataram City, tourism industry players, surrounding communities, and students as agents of change. Activities are carried out in several stages, including observing problems, preparing, implementing waste cleaning, and making recommendations and action plans. The result of this community service activity is the creation of a cleaner and healthier environment, as well as the formation of recommendations and action plans to improve waste management at Loang Baloq Beach and other tourist destinations in Mataram City. The concept of multi-stakeholder collaboration that is applied in this service activity can be an example for waste management activities and the management of other tourist destinations in Indonesia. In addition, this activity also provides valuable experience for students in carrying out community service activities and involving different stakeholders in achieving the same goals. It is hoped that this activity can have a wider impact on the environment and society in Mataram City, and can be used as a reference for similar activities in the future.Keywords: beach destinations; cleanliness; collaboration; garbage; toursAbstrak: Kegiatan pengabdian yang dilakukan merupakan upaya kolaborasi multi stakeholder dalam menjaga kebersihan dan kelestarian Pantai Loang Baloq. Kegiatan dilaksanakan dengan melibatkan berbagai pihak terkait, termasuk Pemerintah Daerah, PDPM Kota Mataram, pelaku industri pariwisata, masyarakat sekitar, dan Mahasiswa sebagai agen perubahan. Kegiatan dilakukan dengan beberapa tahap, antara lain observasi masalah, persiapan, pelaksanaan pembersihan sampah, serta pembuatan rekomendasi dan rencana aksi. Hasil dari kegiatan pengabdian ini adalah terciptanya lingkungan yang lebih bersih dan sehat, serta terbentuknya rekomendasi dan rencana aksi untuk meningkatkan pengelolaan sampah di Pantai Loang Baloq dan destinasi wisata lainnya yang ada di Kota Mataram. Konsep kolaborasi multi stakeholder yang diterapkan dalam kegiatan pengabdian ini dapat menjadi contoh bagi kegiatan pengelolaan sampah dan pengelolaan destinasi wisata lainnya di Indonesia. Selain itu, kegiatan ini juga memberikan pengalaman berharga bagi para mahasiswa dalam melaksanakan kegiatan pengabdian masyarakat dan melibatkan stakeholder yang berbeda dalam mencapai tujuan yang sama. Diharapkan kegiatan ini dapat memberikan dampak yang lebih luas bagi lingkungan dan masyarakat di Kota Mataram, serta dapat dijadikan acuan bagi kegiatan serupa dimasa depan. Kata kunci: destinasi pantai; kebersihan; kolaborasi; sampah; wisata